(untitled) (Scientific journal of the Fergana State University, 2023)
Annotation The article explores the essence and structure of the digital economy and outlines the main directions of changes in the education system in the context of the digital economy. Based on the analysis of the state of e-learning in our country, the main directions of further development of the education system are determined.